Farmer organization, collective action and market access in Meso-America - Lundy, Mark; Meijer, Madelon; Hellin, Jonathan (International Food Policy Research Institute, 2007)
The global agricultural economy is changing. Commodity prices are declining, and producers increasingly supply complex value chains. There is growing interest in how farmers can benefit from emerging market opportunities. Farmers are encouraged to produce high value crops and engage in value-adding activities such as agro-processing. Farmer organization and collective action are often seen as key factors in enhancing farmers’ access to markets. Often too little attention is directed at a) the most appropriate types of organization, b) whether the public and/or private sector is best placed to support their formation, and c) the conditions necessary for ensuring their economic viability. This paper reports on research in Mexico and Central America that explored these issues for commodity maize and high value vegetables respectively. The benefits of farmer organization are more evident in the vegetable sector characterized by high transaction costs associated with market access. The research suggests that farmer organizations established by and directly linked to supermarkets may be more economically sustainable as opposed to organizations supported by non-governmental organizations. However, the most representative vegetable producer organizations in both Honduras and El Salvador include fewer than 5 percent of total horticultural producers. This is due to producer organizations’ limited business skills and non-replicable organizational models for linking producers to markets. There is less incentive for maize farmers to organize themselves to access output markets as the transaction costs associated with market access are relatively low: there are so many buyers and sellers that farmer organizations would have little impact on, for example, prices. The benefits of farmer organization are clearer when it comes to accessing credit, seed, and fertilizer. Farmer organization is a critical factor in making markets work for the poor particularly in high value products, but the role and timing of the substantial public and private investment needed to establish and maintain these organizations is poorly understood.